The study of geometric parameters characterizing the maneuverability of two movable arms of a robotic system - Pritykin, Федор; Chukavov E.A., Чукавов Е.А. (Рroblems of engineering and professional education, 2023)
The study of geometric parameters characterizing the maneuverability of two movable arms of a robotic system